Європейські стандарти гендерної політики в Україні - Горобець, Н. О.; Gorobets, N. O.; ORCID: http://orcid.org/0000-0002-2731-9682 (Юридичний науковий електронний журнал. - 2022. - № 1. - С. 27-29, 2022)
Досліджено впровадження в Україні європейських стандартів гендерної рівності. Проаналізовано Стратегію гендерної рівності Ради Європи на 2018–2023 рр. Констатовано, що забезпечення рівності жінок і чоловіків є одним із головних завдань державної влади. Європейські стандарти недопущення дискримінації за ознакою статі повинні сприяти створенню національного правового інструментарію нетерпимості до гендерної нерівності. Наявні стереотипи суспільної свідомості зумовлюють потребу в осмисленні становища жінки та чоловіка в державі. Помітний прогрес у забезпеченні рівності прав жінок і чоловіків у Європі та Україні не вирішив усі наявні дискримінаційні проблеми. Рівність має розглядатися через рівні можливості та потреби в усіх сферах життєдіяльності, окрім випадків, коли обмеження мають правомірну, об’єктивно обґрунтовану мету.

This article is devoted to the analysis of the implementation of European standards of gender equality in Ukraine. The article analyzes the Council of Europe’s Gender Equality Strategy for 2018–2023. Ensuring equality between women and men is one of the main tasks of state power. European standards for non-discrimination on grounds of sex should contribute to the creation of national legal instruments on gender inequality. Existing stereotypes of public consciousness determine the need to understand the position of women and men in the state. Significant progress in ensuring equal rights for women and men in Europe and Ukraine has not solved all existing discrimination problems. The Gender Equality Strategy for 2018–2023 has six strategic goals. These goals are markers that determine the policy of the state from the standpoint of ensuring equal rights for women and men. Traditional gender stereotypes that still prevail in Ukrainian families are reinforced by media content. The media should be seen as a mirror of gender issues in society. An important step towards the implementation of the Gender Equality Strategy for 2018–2023 in Ukraine is the self-organization of society, cooperation of the public, international institutions and the state. It is important to introduce effective mechanisms to ensure gender equality as an indicator of compliance with European standards of gender policy. Today, mobile teams of social and psychological assistance, crisis rooms, day care centers have been established and are functioning. However, their number is insufficient to cover all victims of women and victims of domestic violence. Only the first steps have been taken, many established institutions are not yet working or there are shortcomings in their work. It is important to realize that equality should not be selective and privileged. Equality must be seen through equal opportunities and needs in all spheres of life, except when restrictions have a legitimate, objectively justified purpose.

Исследовано внедрение европейских стандартов гендерного равенства в Украине. Проанализирована Стратегия гендерного равенства Совета Европы на 2018–2023 гг. Констатировано, что обеспечение равенства женщин и мужчин является одной из главных задач государственной власти. Европейские стандарты недопущения дискриминации по признаку пола должны способствовать созданию национального правового инструментария нетерпимости к гендерному неравенству. Имеющиеся стереотипы общественного сознания обусловливают потребность в осмыслении положения женщины и мужчины в государстве. Заметный прогресс в обеспечении равенства прав женщин и мужчин в Европе и Украине не решил все существующие дискриминационные проблемы. Равенство должно рассматриваться через равные возможности и потребности во всех сферах жизнедеятельности, кроме случаев, когда ограничения имеют правомерную, объективно обоснованную цель.
European standards for gender policy in Ukraine
Горобець, Н. О. Європейські стандарти гендерної політики в Україні [Електронний ресурс ] / Горобець Н. О. // Юридичний науковий електронний журнал. - 2022. - № 1. - С. 27-29. - Режим доступу:http://lsej.org.ua/1_2022/3.pdf.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; гендерна рівність; gender equality; гендерное равенство; європейські стандарти; European standards; европейские стандарты; гендерна політика; gender policy; гендерная политика; Стратегія гендерної рівності; Gender equality strategy; Стратегия гендерного равенства; гендерні стереотипи; gender stereotypes; гендерные стереотипы; гендерна нерівність; gender inequality; гендерное неравенство; Кримінологія. Criminology. Криминология; запобігання; prevention; предотвращение; протидія домашньому насильству; combating domestic violence; противодействие домашнему насилию